2010
DOI: 10.7863/jum.2010.29.7.1023
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency Sonographic Measurements of True and False Vocal Cords

Abstract: Both true and false vocal cords can be shown by high-frequency sonography, which can quantitatively measure both true and false vocal cords with good reliability and reproducibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 17 publications
2
62
1
1
Order By: Relevance
“…There are some previous studies that clearly visualized the oropharyngeal anatomy including vocal folds and boluses in the oropharyngeal area by US examination [14][15][16][17]. The finding in this study that the pharyngeal residue was detected as a misty hyperechoic area above the vocal folds in US images that could be distinguished from the soft tissues around the vocal folds was consistent with these previous studies.…”
Section: Discussionsupporting
confidence: 82%
“…There are some previous studies that clearly visualized the oropharyngeal anatomy including vocal folds and boluses in the oropharyngeal area by US examination [14][15][16][17]. The finding in this study that the pharyngeal residue was detected as a misty hyperechoic area above the vocal folds in US images that could be distinguished from the soft tissues around the vocal folds was consistent with these previous studies.…”
Section: Discussionsupporting
confidence: 82%
“…Both centers achieved an assessability rate of >94%, which seemed to be higher than other series. 10,11,15,16 Furthermore, neither center had a FN (ie, a missed postoperative VCP) on TLUSG. This finding concurred with our previous study, which found TLUSG to be an excellent a screening tool for DL in the postoperative setting.…”
Section: Discussionmentioning
confidence: 98%
“…Hu et al [16] measured wVF of 6.23±0.53 mm in males, and 4.90±0.35 mm in females by ultrasonographic evaluation of the true and false vocal cords. Our findings are consistent with their results.…”
Section: Discussionmentioning
confidence: 99%